Is Cheonggyecheon sustainable? A systematic literature review of a stream restoration in Seoul, South Korea. (February 2019) - Kim, Hyungkyoo; Jung, Yoonhee
Highlights: Sustainability of Cheonggyecheon is assessed. 86 studies on Cheonggyecheon's sustainability is are reviewed and synthesized. Many dimensions of sustainability are yet to be studied. Many of the research findings so far remain mixed or unclear. Abstract: Since its first announcement in 2002 and completion in 2005, restoration of Cheonggyecheon, an urban stream in downtown Seoul, South Korea, has drawn great interest internationally and locally as a model achievement of sustainable development and has triggered extensive empirical research thereafter. This study questions whether the restoration of Cheonggyecheon is sustainable. Using a systematic literature review that combines thematic synthesis and realist review, this study establishes a framework composed of the three Es of sustainable development (environment, economy, and equity) and their 36 dimensions as suggested by literature. Based on the framework, 86 studies published between 2003 and 2017 are reviewed. Results suggest that environmental sustainability is the most studied, while economic sustainability has received the least academic interest. Its equity aspect remains controversial. Overall, it is difficult to confirm Cheonggyecheon's sustainability. Many of its sustainability dimensions require further investigation, and research findings remain mixed or unclear.